(untitled) (Journal of economic and management development research, 2025)
It is intuitively evident that the capacity of artificial intelligence to process knowledge efficiently will bring about a profound transformation to the world. Therefore, questioning such intuitive apprehension serves as a foundation for recognizing the nature of this transformation. Such inquiry necessitates a return to essence—that is, a continuous process of questioning—so as to reveal, on the basis of evidence, the direct reasons underlying this transformation. This requires clarifying the most fundamental concept of being, gradually grasping the ontological structure of being-in-the-world, and then comprehending the concept of political being-in-the-world as it pertains to the transformation. Furthermore, in order to explore the "significance" of artificial intelligence’s transformative capacity, the ontological structure grounded in power discourse must be elucidated. On this basis, the origin and direction of this transformation can be clearly discerned.